Weaning from noninvasive ventilation and high flow nasal cannula in bronchiolitis: A survey of practice. Issue 11 (14th September 2020) - Suzanne, Marie; Amaddeo, Alessandro; Pin, Isabelle; Milési, Christophe; Mortamet, Guillaume
Abstract: Rational: This study aims to describe the current weaning practices from any type of noninvasive support in infants with bronchiolitis, in terms of weaning procedures, weaning initiation and weaning failure criteria. Working Hypothesis: No information regarding the weaning practices is currently available and there may be a wide variability of strategies. Study Design: A cross‐sectional electronic survey. Methodology: The survey was distributed to physicians from five French‐speaking countries with key roles in pediatric intensive care units (PICUs). Results: Responses were obtained from 29 PICUs from five French‐speaking countries. A written weaning protocol was available in three pediatric centers (10%) and nurses had a key role in the weaning process in 72% of centers. The sudden weaning was the most commonly used procedure, no matter the type of noninvasive ventilatory (NIV) support. The most commonly used criteria for weaning initiation and weaning failure were the degree of respiratory distress, the occurrence of apneas and the fraction of inspired oxygen (FiO2 ). The thresholds commonly used for weaning initiation criteria were (a) none or a slight use of accessory muscles; (b) FiO2 less than equal to 40%, (c) respiratory rate less than 60 per minute, (d) no apnea, (e) blood pH more than 7.30, and (f) partial pressure of venous carbon dioxide less than equal to 50 mm Hg. Conclusion: In infants with bronchiolitis requiring NIV support, the sudden weaning procedure was the most commonly used strategy. We observed a certain consensus on criteria for weaning initiation. These findings should help in building nurse‐driven weaning protocols, but prospective studies remain needed to assess the best weaning strategy in infants with bronchiolitis‐related acute respiratory failure.